Macromolecular engineering: from precise macromolecular inks to 3D printed microstructures - Catt, Samantha; Hackner, Maximillian; Spatz, Joachim P.; Blasco, Eva (Small, 2023)
Macromolecules with complex, defined structures exist in nature but rarely is this degree of control afforded in synthetic macromolecules. Sequence-defined approaches provide a solution for precise control of the primary macromolecular structure. Despite a growing interest, very few examples for applications of sequence-defined macromolecules exist. In particular, the use of sequence-defined macromolecules as printable materials remains unexplored. Herein, the rational design of precise macromolecular inks for 3D microprinting is investigated for the first time. Specifically, three printable oligomers are synthesized, consisting of eight units, either crosslinkable (C) or non-functional (B) with varied sequence (BCBCBCBC, alternating; BBCCCBB, triblock; and BBBBCCCC, block). The oligomers are printed using two-photon laser printing and characterized. It is clearly demonstrated that the macromolecular sequence, specifically the positioning of the crosslinkable group, plays a critical role in both the printability and final properties of the printed material. Thus, through precise design and printability of sequence-defined macromolecules, an exciting avenue for the next generation of functional materials for 3D printing is created.
Online veröffentlicht: 20. April 2023
Gesehen am 05.030.2024